2012
DOI: 10.3109/10641963.2012.683912
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of Irbesartan and Olmesartan in Patients With Hypertension (EARTH Study)

Abstract: Fifty-four patients were randomly divided into irbesartan and olmesartan groups. Blood pressure (BP) was significantly decreased in all patients at 12 weeks. In particular, BP in patients who initially received irbesartan showed significant reductions. The equality of variance of BP in the irbesartan group was significantly smaller than that in the olmesartan group at 12 weeks. Blood concentrations of adiponectin were significantly increased in the irbesartan group at 12 weeks. Log [pentraxin-3] in the irbesar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Since the ability of irbesartan to reduce BP was equal to that of olmesartan, the ability of a medium dose of irbesartan (100 mg/day) to reduce BP may be similar to that of a medium dose of olmesartan (20 mg/day). We previously reported that the ability of irbesartan to reduce BP after treatment for 12 weeks is at least comparable to that of olmesartan with equivalent safety (7). The present study also showed a similar result after more long-term treatment for approximately eight months.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Since the ability of irbesartan to reduce BP was equal to that of olmesartan, the ability of a medium dose of irbesartan (100 mg/day) to reduce BP may be similar to that of a medium dose of olmesartan (20 mg/day). We previously reported that the ability of irbesartan to reduce BP after treatment for 12 weeks is at least comparable to that of olmesartan with equivalent safety (7). The present study also showed a similar result after more long-term treatment for approximately eight months.…”
Section: Discussionsupporting
confidence: 78%
“…Irbesartan was also associated with a lower variance of SBP at eight months. There are several possible explanations for this difference in the variance of SBP, which we have discussed in our previous report (7). First, the unique binding behavior of irbesartan is different from that of olmesartan.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…20 Telmisartan may be useful in hypertensive patients with insulin resistance or DM. 21 Nonetheless, in this study, the levels of HbA1c and FBS did not change at three months after a changeover from high-dose telmisartan and HTCZ to high-dose losartan and HTCZ.…”
Section: Discussionmentioning
confidence: 99%